2019
DOI: 10.1111/ddi.12954
|View full text |Cite
|
Sign up to set email alerts
|

Conservation implications of sex‐specific landscape suitability for a large generalist carnivore

Abstract: Aim: Terrestrial mammal distribution models typically do not differentiate between sexes when making spatial predictions, which could have important conservation implications. As male carnivores are usually more risk tolerant and travel longer distances, male potential range should be larger and include more human-modified areas than female range. To evaluate if differences between females and males could influence their conservation planning, we quantified sex-specific suitable range for a recolonizing popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…These models can provide both an understanding of the specific environmental components that might define a species' habitat as well as generate spatial predictions of distribution at a landscape scale (Elith & Leathwick, 2009). Species distribution models have been used extensively to create maps of predicted habitat (Derville et al, 2018; Gantchoff et al, 2019), evaluate threats from climate change or increased anthropogenic disturbance (Diniz‐Filho et al, 2009; Requena‐Mullor et al, 2019), or consider habitat corridors and connectivity (Zeller et al, 2018). Accurate SDMs are particularly important for landscape‐scale conservation planning given the large‐scale changes associated with climate (Park Williams et al, 2013), anthropogenic alterations (Curtis et al, 2018), habitat loss and fragmentation (Sala et al, 2000), wildfire (Hansen et al, 2010), and insect outbreaks (Kurz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These models can provide both an understanding of the specific environmental components that might define a species' habitat as well as generate spatial predictions of distribution at a landscape scale (Elith & Leathwick, 2009). Species distribution models have been used extensively to create maps of predicted habitat (Derville et al, 2018; Gantchoff et al, 2019), evaluate threats from climate change or increased anthropogenic disturbance (Diniz‐Filho et al, 2009; Requena‐Mullor et al, 2019), or consider habitat corridors and connectivity (Zeller et al, 2018). Accurate SDMs are particularly important for landscape‐scale conservation planning given the large‐scale changes associated with climate (Park Williams et al, 2013), anthropogenic alterations (Curtis et al, 2018), habitat loss and fragmentation (Sala et al, 2000), wildfire (Hansen et al, 2010), and insect outbreaks (Kurz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While the impact of sample size on SDMs has been extensively considered, the general concern has been with too little data, rather than too much (Hernandez et al, 2006; Stockwell & Peterson, 2002). However, the recent availability of extensive Global Positioning System (GPS) datasets presents a novel challenge to conventional SDMs as there is little consensus regarding how to treat the large volume of animal relocations (Gantchoff et al, 2019; Li et al, 2017; Magg et al, 2016; Maiorano et al, 2015; Rice et al, 2013; Shoemaker et al, 2018) which may create redundant or spatially correlated nonindependent information with respect to species distributions, particularly if few animals are sampled. Yet, GPS data provide high spatial accuracy, reduced sampling bias, and less species misidentification; all these issues plague the opportunistic sampling schemes common in SDM literature (Aubry et al, 2017; Newbold, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We used GPS telemetry data (2011–2018) from 97 individual bears which were located in and around the Ozarks highlands (~41,078 km 2 of south‐central Missouri), and collected as part of the Missouri Black Bear Project (see Gantchoff et al., 2019 for capture and collaring methods). All capturing and handling of bears followed the American Society of Mammalogists guidelines (Sikes et al., 2016) and was approved by the Mississippi State University (protocols 13‐094 and 17‐431) and the State University of New York (protocol 180504) Institutional Animal Care and Use Committees.…”
Section: Methodsmentioning
confidence: 99%
“…Ditmer et al observed bears at the edge of their range within a sparsely-forested area of Minnesota (considered atypical bear habitat) and used short time windows of habitat use by collared bears to try to predict the minimum amount of forest that they could tolerate; they used this to gauge how far west across a gradient of decreasing forest the population could expand [205]. Gantchoff et al argued that habitat models could over-estimate the potential range if the sexes are pooled, because females in their expanding population in Missouri were observed to be more constrained to less human-developed areas than males [221]. However, their frame of reference for what females could tolerate was based on where females lived currently.…”
Section: American Black Bearsmentioning
confidence: 99%